Modelagem matemática de cloro residual em redes dedistribuição de água : estudo de caso no Jardim Higienópolis em Maringá-PR - Junqueira, Rodrigo Fernandes (2010)
This experiment presents a study of a mathematical calibrating model that represents the values of pressure and chlorine concentration at the join of the water distribution network when oscillations occurs in water demand. Seven points were used to monitor the pressure and three points to monitor the concentration of residual chlorine. To calibrate the pipe roughness coefficients and the demands at the join, had been used the genetic algorithm method. The demand curve that was used in this experiment was obtained by the informations of the exit reservoirs flow monitoring of the studied region. Then it was determined the chlorine decay to the water study. The results were satisfactory for the hydraulic model with good approximation in 06 of 07 points monitored. By the results of spatial distribution, was possible to identify regions with high pressures that can be reduced with the installation of pressure reducing valves. For the concentration of chlorine, the model describes the oscillations in the concentration, however in the large amplitudes the model can not approximate the observed values.